GIS and Remote Sensing for Renewable Energy Assessment and Maps - Nastasi, Benedetto; Nezhad, Meysam Majidi (MDPI, 2022)
This book aims at providing the state-of-the-art on all of the aforementioned tools in different energy applications and at different scales, i.e., urban, regional, national, and even continental for renewable scenarios planning and policy making.